Alzheimer’s disease induced neurons bearing PSEN1 mutations exhibit reduced excitability - Maksour, Simon; Finol-Urdaneta, Rocio K.; Hulme, Amy J.; Cabral-da-Silva, Mauricio e Castro; Targa Dias Anastacio, Helena; Balez, Rachelle; Berg, Tracey; Turner, Calista; Sanz Muñoz, Sonia; Engel, Martin; Kalajdzic, Predrag; Lisowski, Leszek; et al. (Frontiers in Cellular Neuroscience, 2024)
Alzheimer's disease (AD) is a devastating neurodegenerative condition that affects memory and cognition, characterized by neuronal loss and currently lacking a cure. Mutations in PSEN1 (Presenilin 1) are among the most common causes of early-onset familial AD (fAD). While changes in neuronal excitability are believed to be early indicators of AD progression, the link between PSEN1 mutations and neuronal excitability remains to be fully elucidated. This study examined iPSC-derived neurons (iNs) from fAD patients with PSEN1 mutations S290C or A246E, alongside CRISPR-corrected isogenic cell lines, to investigate early changes in excitability. Electrophysiological profiling revealed reduced excitability in both PSEN1 mutant iNs compared to their isogenic controls. Neurons bearing S290C and A246E mutations exhibited divergent passive membrane properties compared to isogenic controls, suggesting distinct effects of PSEN1 mutations on neuronal excitability. Additionally, both PSEN1 backgrounds exhibited higher current density of voltage-gated potassium (Kv) channels relative to their isogenic iNs, while displaying comparable voltage-gated sodium (Nav) channel current density. This suggests that the Nav/Kv imbalance contributes to impaired neuronal firing in fAD iNs. Deciphering these early cellular and molecular changes in AD is crucial for understanding disease pathogenesis.